The Impact of The Dissemination of The Covid-19 Epidemic on Social Development in Early Children - Najamuddin, Najamuddin; Sahrip, Sahrip; Siahaan, Kevin William Andri; Yunita, Widia; Ananda, Rizki (International Journal of Elementary Education, 2022)
With the spread of the Covid-19 outbreak, such as an epidemic in the world, the policy of maintaining physical distance (physical distance) and social distance (social distance) has changed the pattern of life in all fields. The world of education at all levels, including early childhood education (PAUD), also feels the impact. Studying at home with an online system is an indispensable option, creating new problems in the field of education. This study aims to analyze the impact of the Covid-19 outbreak on the social development of early childhood. This research uses a qualitative descriptive research type. Data collection techniques using interviews, observation, and documentation. The technique used to ensure the validity of the data uses the source and time triangle, while the analytical technique used in this study is a qualitative analysis technique. The final results of this study indicate that the influence of Covid-19 on the social development of early childhood requires the government to issue a policy of implementing community activity restrictions (PPKM) which causes children to study from home and consequently has an impact on children's development such as cognitive development, language, and development early childhood social.